The Impact of Prolonged Mechanical Ventilation on Overall Survival in Patients With Surgically Treated Brain Metastases - Schuss, Patrick; Schäfer, Niklas; Bode, Christian; Borger, Valeri; Eichhorn, Lars; Giordano, Frank A.; Güresir, Erdem; Heimann, Muriel; Ko, Yon-Dschun; Landsberg, Jennifer; Lehmann, Felix; Potthoff, Anna-Laura; et al. (Frontiers in Oncology, 2021)
Objective: Surgical resection represents a common treatment modality in patients with brain metastasis (BM). Postoperative prolonged mechanical ventilation (PMV) might have an enormous impact on the overall survival (OS) of these patients suffering from advanced cancer disease. We therefore have analyzed our institutional database with regard to a potential impact of PMV on OS of patients who had undergone surgery for brain metastases. Methods: 360 patients with surgically treated brain metastases were included. The definition of PMV consisted of postoperative mechanical ventilation lasting for more than 48 hours. Analysis of survival incorporating established prognostic factors such as age, location of BM, and preoperative physical status was performed. Results: 14 of 360 patients with BM (4%) suffered from postoperative PMV after surgical treatment of BM. Patients with PMV presented in a significantly more impaired neurological condition preoperatively than patients without (p<0.0001). Multivariate analysis determined PMV to be a significant prognostic factor for OS after surgical treatment in patients with BM, independent of other predictive factors (p<0.0001). Conclusions: The present study demonstrates postoperative PMV as significantly related to poor OS in patients with surgically treated BM. Postoperative PMV is a so far underestimated prognostic predictor, but might be utilized for optimized patient management early in the postoperative phase. For this purpose, the results of the present study should encourage the initiation of further scientific efforts.